COVID19 in hematological patients and telemedicine: lessons learned across Europe and the US. Issue 4 (5th August 2022) - Mussetti, Alberto; Peric, Zinaida; Figueroa, Cesar
Abstract : Purpose of review: To describe the state-of-the-art of telemedicine in hematology through the description of most relevant studies published in the pre-COVID19 and during the COVID19 era. Recent findings: Telemedicine has recently gained momentum in hematology due to the COVID19 pandemic. Due to a necessary improvement of domiciliary follow-up of patients during the pandemic and an increase in technologies able to offer telemedicine, the number of studies has increased in the last 2 years. Telemedicine showed the potential to improve the monitoring of both benign and malignant hematological diseases. Patients affected by thalassemias, hemophilias and/or myeloproliferative diseases were monitored successfully with telemedicine platform. For higher-risk patients such as high-dose chemotherapy or stem cell transplantation, better platforms are needed (e.g. use of wearable devices systems). Also, telemedicine showed to be useful for the follow-up of hematological patients with COVID19. Summary: Despite the clear potential advantages of telemedicine for the follow-up of hematological patients, more evidence is required before adopting this approach in larger cohorts of patients. Larger- and higher-quality studies are highly needed in this setting.